The Everyday Emotional Experience of Adults with Major Depressive Disorder: Examining Emotional Instability, Inertia, and Reactivity - Thompson, Renee J. (2012)
Investigators have begun to examine the temporal dynamics of affect in individuals diagnosed with Major Depressive Disorder (MDD), focusing on instability, inertia, and reactivity of emotion. How these dynamics differ between individuals with MDD and healthy controls have not before been examined in a single study. In the present study, 53 adults with MDD and 53 healthy adults carried hand-held electronic devices for approximately seven days and were prompted randomly eight times per day to report their levels of current negative affect (NA), positive affect (PA), and the occurrence of significant events. In terms of NA, compared with healthy controls, depressed participants reported greater instability and greater reactivity to positive events, but comparable levels of inertia and reactivity to negative events. Neither average levels of NA nor NA reactivity to, frequency or intensity of, events accounted for the group difference in instability of NA. In terms of PA, the MDD and control groups did not differ significantly in their instability, inertia, or reactivity to positive or negative events. These findings highlight the importance of emotional instability in MDD, particularly with respect to NA, and contribute to a more nuanced understanding of the everyday emotional experiences of depressed individuals.